Complications of Facial Trauma of the Fronto-orbital Region - Cleveland, Patrick W.; Smith, Jesse Ellis (Facial Plastic Surgery, 2017)
Traumatic injuries to the orbitofrontal region place some of the most important structures of the face at risk: the eyes, frontal skull, and brain. A thorough knowledge of complications from resultant trauma, and from attempted surgical corrections, is necessary to offer patients the best outcomes, ensuring proper healing with excellent long-term results.
Keywords: orbital; frontal sinus; complications; frontal sinus fractures; orbital fractures